Exploring the Nexus of Token Acts of Online Support, Compassion, and Behavioral Intentions Toward Immigrants from Ukraine and Russia - Nonna Kushnirovich; Sabina Lissitsa (Behavioral Sciences)
This study investigates the relationship between public token acts of online support and prosocial behavioral intentions, shedding light on the potential mediating influences that contribute to this intricate interplay. It focuses on the determinants of prosocial behavioral intentions toward three specific groups of immigrants who came to Israel after Russia’s invasion of Ukraine in 2022: asylum seekers from Ukraine, immigrant citizens repatriated from Ukraine, and immigrant citizens repatriated from Russia. The data were collected via a survey of 847 social media users in Israel. This study revealed that the higher the frequency of token acts of online support for prosocial content in social media, the higher perspective-taking and emotional concerns were reported by respondents. High emotional concern, in turn, was associated with higher prosocial behavioral intentions. Summing up, the more actively people engage with prosocial content on social media, the higher their prosocial behavioral intentions are.